Beyond Intercalation Chemistry for Rechargeable Mg Batteries: A Short Review and Perspective - Zhao-Karger, Zhirong; Fichtner, Maximilian (Frontiers in Chemistry, 2019)
Rechargeable magnesium (Mg) batteries are an attractive candidate for next-generation battery technology because of their potential to offer high energy density, low cost, and safe use. Despite recent substantial progress achieved in the development of efficient electrolytes, identifying high-performance cathode materials remains a bottleneck for the realization of practical Mg batteries. Due to the strong interaction between the doubly charged Mg2+ ions and the host matrix, most of the conventional intercalation cathodes suffer from low capacity, high voltage hysteresis, and low energy density in Mg based battery systems. Alternatively, the thermodynamically favorable conversion reaction may circumvent the sluggish Mg2+ diffusion kinetics. In this review, the focus will be laid on promising cathodes beyond the typical intercalation-type materials. We will give an overview of the recent emerging Mg systems with conversion-type and organic cathodes.